Enhancing Neurology Clinic Efficiency through Agile-Based Inventory Management System for Medical Supplies - Sihombing, Denny Jean Cross (Jurnal Ekonomi, 2024)
This study aims to enhance the efficiency of neurology clinics by implementing an Agile-based inventory management system for medical supplies. The identified problem is the need for more efficiency in managing medical supply inventory, which can lead to stock shortages, management errors, and delays in patient care. The methodology employed is an Agile approach in software development, starting from user needs analysis and application development to user acceptance evaluation. This research indicates the system's success in improving clinic efficiency by enhancing inventory management performance, improving the efficiency of medical supply procurement processes, reducing stock management errors, and enhancing user satisfaction. The contribution of this research lies in its theoretical implications for inventory management theory development in the healthcare field and its practical implications for efficient neurology clinic management. Suggestions for further research include exploring the integration of other technologies, such as Artificial Intelligence (AI) and the Internet of Things (IoT), to enhance automation and more sophisticated data management in healthcare inventory management systems. Thus, this research contributes significantly to developing adaptive and efficient inventory management systems in neurology clinics, which can serve as a foundation for further innovation in the healthcare industry